The Effect of Live Streaming, Hedonic Shopping, and Shopping Lifestyle on Impulsive Buying Through Price Discounts - Sihaloho, Ronal Donra; Silahahi, Meslin; Handayani, Rina; Simanullang, Artika May (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Tik-Tok Shop is a social media application that is widely liked by almost all levels of society, including young people, including regular students of Sisingamangaraja XII Tapanuli University (UNITA). Many features are available in the Tik-Tok application, including tik-tok shop, which is given the convenience of conducting product/service buying and selling transactions such as live streaming , price discounts that can hypnotize all consumers. Where initially just browsing, then continued to become impulsive buying and this will eventually become hedonic shopping and shopping lifestyle so that it has an impact on high consumption. The number of samples used in this study was 86 people, using non-probability sampling techniques and using purposive sampling methods . The data analysis method used is path analysis with SEM ( Structural Equation Modeling). The results of the study show that partially Live Streaming has no significant effect on Impulsive Buying , partially Live Streaming has a significant effect on Price Discount , partially Hedonic Shopping has a significant effect on Impulsive Buying , partially Hedonic Shopping has a significant effect on Price discount , partially Shopping Lifestyle has a significant effect on Impulsive Buying , partially Shopping Lifestyle has a significant effect on Price Discount , partially Price Discount has a significant effect on Impulsive Buying . Live Streaming has a significant indirect effect on Impulsive Buying through Price Discount as an Intervening variable , Hedonic Shopping has a significant indirect effect on Impulsive Buying through Price Discount as an Intervening variable , and Shopping Lifestyle has a significant indirect effect on Impulsive Buying through Price Discount as an Intervening variable